AN ANALYSIS OF TRANSLATION TECHNIQUES IN MEDICAL NEWS TODAY ENTITLED Ã¢â‚¬Å“WHAT TO KNOW ABOUT MALARIAÃ¢â‚¬Â - GRENDI PUTRI K., ORVIN (Fakultas Bahasa dan Sastra Universitas PGRI Kanjuruhan Malang, 2022)
The aim of conducting this study is to find and analyze the translation techniques used in medical text in form of article entitled what to Know about Malaria. In examining the translation of the text, this study uses the translation techniques proposed by Vinay and Darbelnet. This is a descriptive qualitative study using document analysis that consists of finding, selecting, appraising (making sense of), and synthesizing data contained in documents (Bowen, 2009). The result of the study shows that the dominant technique used in translating the text is literal translation with the percentage 31.25% followed by borrowing which is 25%. Literal translation is mostly used since some parts of the text contain simple structures that is easier to be translated directly. Meanwhile, borrowing relates to the use of medical terms in the text. Some terms have longer forms when they are translated into TT (Indonesian), so that borrowing is used to make it more efficient.